Metabolic assessment in patients with urinary lithiasis - Amaro, Carmen R. [UNESP]; Goldberg, José [UNESP]; Amaro, João Luiz [UNESP]; Padovani, Carlos Roberto [UNESP] (Sociedade Brasileira de Urologia, 2005)
INTRODUCTION: Metabolic investigation in patients with urinary lithiasis is very important for preventing recurrence of disease. The objective of this work was to diagnose and to determine the prevalence of metabolic disorders, to assess the quality of the water consumed and volume of diuresis as potential risk factors for this pathology. PATIENTS and METHODS: We studied 182 patients older than 12 years. We included patients with history and/or imaging tests confirming at least 2 stones, with creatinine clearance > 60 mL/min and negative urine culture. The protocol consisted in the collection of 2, 24-hour urine samples, for dosing Ca, P, uric acid, Na, K, Mg, Ox and Ci, glycemia and serum levels of Ca, P, Uric acid, Na, K, Cl, Mg, U and Cr, urinary pH and urinary acidification test. RESULTS: 158 patients fulfilled the inclusion criteria. Among these, 151 (95.5%) presented metabolic changes, with 94 (62.2%) presenting isolated metabolic change and 57 (37.8%) had mixed changes. The main disorders detected were hypercalciuria (74%), hypocitraturia (37.3%), hyperoxaluria (24.1%), hypomagnesuria (21%), hyperuricosuria (20.2%), primary hyperparathyroidism (1.8%) secondary hyperparathyroidism (0.6%) and renal tubular acidosis (0.6). CONCLUSION: Metabolic change was diagnosed in 95.5% of patients. These results warrant the metabolic study and follow-up in patients with recurrent lithiasis in order to decrease the recurrence rate through specific treatments, modification in alimentary and behavioral habits.
Keywords: urolithiasis; risk factors; salts; metabolic disease; follow-up; studies